PRODUCTION TECHNOLOGY IMPROVEMENT AND “RENGGINANG” PACKAGING REDESIGN IN GELUNG VILLAGE, PANARUKAN DISTRICT, SITUBONDO REGENCY - nur lailatul rahmah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2017)
Gelung Village is one of the center of craftsmen Rengginang in the Panarukan district, Situbondo Regency East Java. Obstacles that faced by craftsmen were unevenness of Rengginang shape, quantity (net weight of each pack), packaging and labeling. It not have fulfilled requirements for a review of the food safety packaging, so it has markets limited. That activities gave facility of Rengginang mould tool, digital scales, and handsealer, plastic packaging materials as primary packaging, label Cardboard as secondary packaging as well as transport packaging for promotion. The results of this activities were: Rengginang has round shape and uniform dimension, uniform weight rengginang, Rengginang packaging has accordance with criteria for Food Safety. In addition, there were improvement of packaging design and markettable of label (to avoid of duplicity brand by unresponsible parties) As well as the open mind of Insight as well as the partners of the importance of brand Expansion Markets. SMEs Rengginang Brand Ibu Haris Kejora and Bagaskara has marketed successfully of Rengginang Product in Situbondo Souvenir Central Market by increasing Rp.1.500,- each carton.